The practice of the Investigation process: the impact of cognitive conflict on the improvement of the training of concept «Composition of inspired air and expired air» for the pupils of primary cycle. - Khelifi, Bilel (Advances in Social Sciences Research Journal, 2021)
The first one left this research concerns the place of cognitive conflict in the Investigation on the alert scientific at the level of primary education. The second part is interested in the impact of cognitive conflict on the improvement of training. The methodology rests the basics on a question put down to the pupils of sixth primary year in different Tunisian schools by the way the composition of air which they inspire and that of the air which is expired. Answers given by the pupils show well that there is a problem linked to previous erroneous conception. Our research aims at improving the training of this concept by cognitive conflict. Therefore, we worked out for the pupils an experience based on observation and text given to every pupil allowing a cognitive conflict and objective is to cause a conceptual change. Obtained results show a positive impact of cognitive conflict on the acquisition of this concept and training improvement.